The current status of miRNA in urinary bladder cancer: A minireview and strength, weakness, opportunity, and threat analysis - Rachana Tripathy; Lalit Kumar; Sukhad Kural; Anuja Thakur; Sameer Trivedi; Satya Narayan Sankhwar (Indian Journal of Urology)
MicroRNAs, small noncoding RNA molecules, are critical in modulating gene expression and contribute substantially to the initiation and progression of urinary bladder cancer (UBCa), a major malignancy affecting people globally. UBCa is known for its high recurrence rates and significant heterogeneity. The stability of miRNAs in body fluids such as urine and blood are excellent potential noninvasive markers for early detection, monitoring treatment progress, and predicting outcomes of patients with UBCa. In addition, miRNAs could also improve the effectiveness of immunotherapy and support the development of personalized treatment strategies. Despite their significant potential, challenges such as variability in the expression of miRNAs and shortcomings in their delivery systems must be carefully addressed. This strength, weakness, opportunity, and threat (SWOT) analysis highlights the crucial role of miRNAs in UBCa and explores their potential in advancing precision oncology.